Disgust and its disorders : theory, assessment, and treatment implications - McKay, Dean, 1966-; Olatunji, Bunmi O. (American Psychological Association, 2009)
"In recent years there has been a surge of research on disgust and its relation to phobic avoidance. This comprehensive volume provides the first extensive, up-to-date compilation of information available on this emotion. Disgust and its disorders: Theory, assessment, and treatment implications thoughtfully examines the role of disgust in psychopathology by highlighting important theoretical and methodological developments and discussing recent research on behavioral patterns that can be provoked by disgust. Contributors demonstrate that disgust plays an important role in a wide range of psychopathology, including sexual dysfunction, eating disorders, animal phobias, and obsessive-compulsive disorder. Disgust is shown to be a multidimensional construct that centers on the unifying theme of potential contamination of the body, soul, and broad social order. Editors Bunmi O. Olatunji and Dean McKay thoroughly review the available research on disgust and shed light on how its interpretation will, in turn, facilitate the development of better treatment of disgust-related avoidance"--Jacket. (PsycINFO Database Record (c) 2009 APA, all rights reserved)